The Effects of Temperature and Velocity of Exhaust Gas on NO Absorption and H2O2 Conversion to Nitric Acid - Kanberoglu, Berna; Gonca, Guven (SPRINGER HEIDELBERG, 2025)
Reducing NOx emissions from fuels is critical to reducing air pollution and promoting environmental sustainability, particularly in the maritime industry. This study investigates the effectiveness of NO absorption in a hydrogen peroxide solution as a potential method for reducing NO emissions in marine exhaust systems. Numerical analyses were performed using the computational fluid dynamics (CFD) method to simulate the chemical interaction between exhaust gases and H2O2 under varying conditions. In this context, the study analyzed the effect of varying exhaust gas velocity, temperature and NO mass fraction in the ranges of 0.01-10 m/s, 288-573 degrees C and 0.001-0.5, respectively, on NO absorption efficiency and nitric acid formation. The results indicate that higher temperatures enhance NO conversion efficiency, reaching its peak at 573 degrees C due to accelerated reaction kinetics. However, increasing exhaust gas velocity negatively affects NO absorption, reducing its overall effectiveness. These findings provide valuable insights for optimizing NOx removal processes in marine applications and contribute to the development of strategies compliant with IMO Tier III emission regulations.
Keywords: NOx reduction; H2O2 absorption; CFD; Ship emissions; NITROGEN; REMOVAL; AMMONIA; DESIGN; OXIDE; Science & Technology - Other Topics